Strengthening the role of universities in the national agricultural research systems in sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Strengthening the role of universities in the national agricultural research systems in sub-Saharan Africa